Pain Asymbolia as Depersonalization for Pain Experience. An Interoceptive Active Inference Account - Gerrans, Philip (Frontiers in Psychology, 2020)
“The feeling that our subjective experiences are bound to a ‘real me’ or ‘self’ inside our body is a key feature of the human mind”. “Mineness “ also called “Subjective Presence” or “Personalisation” is the feeling that experiences belong to a continuing self. This paper argues that the mineness is produced by processes of interoceptive active inference that model the self as the underlying cause of continuity and coherence in affective experience. A key component of this hierarchical processing system, and hub of affective self-modeling is activity in the anterior insula cortex. I defend the account by applying it to the phenomenon of pain asymbolia, a condition in which nociceptive signals (of bodily damage) are not attributed to the self. Thus pain asymbolia is a form of “depersonalisation for pain” as Klein puts it. The pain is experienced as happening to my body but is not experienced as mine. Thus we can describe it as loss of subjective presence or “mineness” for the experience of pain.